2005
DOI: 10.1213/01.ane.0000136771.64552.9c
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Isovolemic Hemodilution on Oxygenation During One-Lung Ventilation

Abstract: Data on the effects of isovolemic hemodilution (IH) on oxygenation during one-lung ventilation (OLV) are lacking. We studied 47 patients with hemoglobin >14 g/dL who were scheduled for lung surgery (17 with normal lung function [group NL], 17 with chronic obstructive pulmonary disease [COPD] [group COPD], and 13 with COPD as control for time/anesthesia effects [group CTRL]). Anesthesia was standardized. The tracheas were intubated with a double-lumen tube. Ventilatory settings and fraction of inspired oxygen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Unfortunately, the design of our study did not allow us to measure shunt fraction directly; it was a purely clinical study on patients undergoing thoracic surgery, and according to institutional structures, monitoring and measurements were limited, with no ethical and economical justification for more invasive monitoring in these patients. However, the shunt and changes in pulmonary blood flow were quantified based on the PaO 2 values from Nunn's iso‐shunt lines 18 . The mean shunt during supine OLV was about 25%, during D‐OLV 20% and during ND‐OLV 30%, suggesting that the change in pulmonary blood flow from supine to lateral is a 5% increase in the dependent lung and 5% decrease in the non‐dependent lung.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the design of our study did not allow us to measure shunt fraction directly; it was a purely clinical study on patients undergoing thoracic surgery, and according to institutional structures, monitoring and measurements were limited, with no ethical and economical justification for more invasive monitoring in these patients. However, the shunt and changes in pulmonary blood flow were quantified based on the PaO 2 values from Nunn's iso‐shunt lines 18 . The mean shunt during supine OLV was about 25%, during D‐OLV 20% and during ND‐OLV 30%, suggesting that the change in pulmonary blood flow from supine to lateral is a 5% increase in the dependent lung and 5% decrease in the non‐dependent lung.…”
Section: Discussionmentioning
confidence: 99%
“…In physiologic studies, Deem et al 80 showed that shunt fraction increases and oxygenation decreases with low hemoglobin levels. Szegadi et al 81 studied the effects of acute hemodilution on oxygenation in patients with and without chronic pulmonary obstructive disease undergoing OLV. They found that acute removal of 500 ml blood did not affect oxygenation in the normal population, whereas it decreased oxygenation in patients with chronic obstructive pulmonary disease.…”
Section: Hemoglobin Levelsmentioning
confidence: 99%
“…Little research has, however, been conducted as to how changes in Hb indeed affect arterial oxygenation during OLA. Szegedi and colleagues [51] assessed the effects of acute normovolemic hemodilution on arterial oxygen tensions during OLA in patients with and without chronic obstructive pulmonary disease (COPD). After hemodilution, patients who had COPD exhibited decreases in PaO 2 , whereas there were no changes in subjects with normal lungs, or in the control group with COPD who did not undergo hemodilution.…”
Section: Cco 2 and Ola: The Effect Of Hemoglobin Concentrationmentioning
confidence: 99%